The Influence of Social Media Marketing Strategy on Purchase Intention with the Mediating Variables of Brand Image and Brand Awareness on Types of Travel Insurance Products in Indonesia - Purba, Desima Fitriani; Jahja, Adi Susilo (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to examine the influence of Social Media Marketing on Purchase Intention using the mediating variables Brand Image and Brand Awareness on travel insurance products in Indonesia. It is hoped that through this research we can find out how far the impact of social media marketing is on increasing purchasing decisions for travel insurance products. The sampling method used was purposive sampling involving 240 respondents which was carried out using the questionnaire method. Quantitative analysis includes outer model analysis, inner model analysis and hypothesis testing. The research results show that: (1) Social Media Marketing has a positive and significant influence on Purchase Intention; (2) Social Media Marketing has a positive and significant influence on Brand Image; (3) Social Media Marketing has a positive and significant influence on Brand Awareness; (4) Brand Image has a positive and significant influence on Purchase Intention; (5) Brand Awareness has a positive and significant influence on Purchase Intention; (6) Brand Image mediates the relationship between Social Media Marketing and Purchase Intention; (7) Brand Awareness mediates the relationship between Social Media Marketing and Purchase Intention